Development of a Psychometric Instrument for Creativity Potential and Art Appreciation - Pratamawati, E.W Suprihatin Dyah; Rahayuningsih, Sri; Nasir, Farah Damia Mohd (Jurnal Riset dan Inovasi Pembelajaran, 2025)
This study aims to develop a valid and reliable instrument to measure creativity potential and art appreciation among students enrolled in the Arts and Culture Teacher Professional Education Program (PPG). The research was driven by the limited availability of assessment tools that comprehensively measure non-technical competencies, particularly creative thinking and aesthetic responsiveness, which are essential components in arts education. Employing a Research and Development (R&D) approach, this study adopted a modified Borg and Gall model consisting of seven stages, including needs analysis, blueprint formulation, item development, expert judgment for content validation, pilot testing, revisions, and large-scale field testing. Data were collected using a Likert-scale questionnaire and performance-based assessment tasks. Content validity was analyzed using Aiken’s V, while construct validity was tested through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Reliability was established using Cronbach’s Alpha, McDonald’s Omega, and Intraclass Correlation Coefficient (ICC). The findings confirmed that the developed instrument met strong psychometric standards, with factor loadings aligned with theories of creativity and contemporary aesthetics. The instrument effectively captures five dimensions of creativity (fluency, flexibility, originality, elaboration, and creative self-efficacy) and five dimensions of art appreciation (formal perception, interpretation, evaluation, transformational reflection, and tolerance of ambiguity). This instrument can serve as a diagnostic and evaluative tool and provide pedagogical insights for enhancing creative and reflective learning in arts education.